2015
DOI: 10.1007/s10897-015-9894-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Distress After Genetic Testing for Hereditary Cancer

Abstract: The psychological impact of an unfavorable genetic test result for counselees at risk for hereditary cancer seems to be limited: only 10–20 % of counselees have psychological problems after testing positive for a known familial mutation. The objective of this study was to find prognostic factors that can predict which counselees are most likely to develop psychological problems after presymptomatic genetic testing. Counselees with a 50 % risk of BRCA1/2 or Lynch syndrome completed questionnaires at three time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 33 publications
2
37
1
2
Order By: Relevance
“…As expected, and in line with literature, we found that individuals in our sample had higher levels of anxiety and depressive symptoms; the levels were clinically significant, suggesting possible psychological disorder that should be further investigated. This is consistent with results obtained in previous research (Heshka et al 2008;Smerecnik et al 2009;Voorwinden and Jaspers 2016).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…As expected, and in line with literature, we found that individuals in our sample had higher levels of anxiety and depressive symptoms; the levels were clinically significant, suggesting possible psychological disorder that should be further investigated. This is consistent with results obtained in previous research (Heshka et al 2008;Smerecnik et al 2009;Voorwinden and Jaspers 2016).…”
Section: Discussionsupporting
confidence: 94%
“…Instead, other studies have reported that psychological distress (in particular, cancer-specific-distress) was significantly associated with refusal or withdrawal from genetic counselling, whether levels of distress were high or low. A moderate level of distress (general distress and cancer-specific-distress) was found to facilitate the decision to undergo genetic counselling (Cabrera et al 2010;Christie et al 2012;Voorwinden and Jaspers 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who tested negative for a pathogenic variant had a median total score of 15 (IQR, [9][10][11][12][13][14][15][16][17][18][19][20][21][22], which was not significantly different from that of patients who tested positive (20; IQR, 14-26 [P = .057]). The median total MICRA score among those patients with a VUS genetic testing result was 18 (IQR, [15][16][17][18][19][20][21][22][23][24], which also was not significantly different from the score for patients receiving positive results (P = .43). Scores for the Uncertainty and Cancer Experience subscales in patients with a VUS genetic testing result (3 [IQR, 0-6] and 5 [IQR, 3.5-5], respectively) were significantly different from Cancer July 15, 2019 those of patients receiving positive results (6 [IQR, 3.5-10; P = .017] and 2 [IQR, 0-4; P = .002], respectively).…”
Section: Micra Scoresmentioning
confidence: 99%
“…Given the natural stress of a new cancer diagnosis, there is understandable concern about adding additional distress through genetic testing. In prior studies of germline genetic testing in patients with cancer, only a small minority of patients have been shown to experience psychological distress after testing and, when present, these feelings do not persist long‐term . The Multidimensional Impact of Cancer Risk Assessment (MICRA) questionnaire is a standardized tool that has identified sources of distress from genetic testing in both patients with cancer and other at‐risk groups in multiple studies …”
Section: Introductionmentioning
confidence: 99%